Peran Hadroh Sebagai Sarana Pembentukan Karakter Santri Melalui Seni Islam di Madrasah Pertubuhan Kebajikan Almuhibbin Malaka Malaysia - Rizki Pratama, T Aldi; Abrianto, Danny; Sulaiman, Rahmad; Siddik, Ahmad Nur; Fikri, Aidil (Innovative: Journal Of Social Science Research, 2025)
Data collection in the form of observation, interviews and documentation. Data analysis includes data collection, data provision, and total images. The results of the study showed that, Instilling Islamic Educational Values ​​Through Hadroh Art at the Hidayatul Mubtadiin Sidoharjo Jati Agung Islamic Boarding School, using the strategy of prioritizing the Prophet as the messenger of Allah SWT, chanting prayers and religious/Islamic poetry, Small talk taking the theme of the noble attitude of the Prophet SAW such as the story of the Prophet's struggle when preaching, and practicing the sunnahs of the Prophet SAW, The Impact of Instilling Islamic Educational Values ​​Through Hadroh Art at Almuhibbin malaka Malaysia Islamic Boarding School, choosing an educational institution based on an Islamic boarding school with out coercion, liking the Prophet's prayers and poetry with religious and Islamic nuances, reducing the habit of using rude and dirty words, and being able to emulate the noble attitude of the Prophet, some of the obstacles faced are Activities that lasted until late at night, making the students wake up later than usual or oversleep when trying to perform the obligatory prayer activities congregation at dawn so many were late or even drunk not praying at dawn, in Madrasah Pertubuhan Kebajikan Almuhibbin Malaka, Malaysia